Cellular‐specific role of toll‐like receptor 4 in hepatic ischemia‐reperfusion injury in mice123. Issue 1 (27th May 2013) - Nace, Gary W.; Huang, Hai; Klune, John R.; Eid, Raymond E.; Rosborough, Brian R.; Korff, Sebastian; Li, Shen; Shapiro, Richard A.; Stolz, Donna B.; Sodhi, Chhinder P.; Hackam, David J.; Geller, David A.; et al.
Abstract Ischemia‐reperfusion (I/R) injury is a process whereby an initial hypoxic insult and subsequent return of blood flow leads to the propagation of innate immune responses and organ injury. The necessity of the pattern recognition receptor, Toll‐like receptor (TLR)4, for this innate immune response has been previously shown. However, TLR4 is present on various cell types of the liver, both immune and nonimmune cells. Therefore, we sought to determine the role of TLR4 in individual cell populations, specifically, parenchymal hepatocytes (HCs), myeloid cells, including Kupffer cells, and dendritic cells (DCs) subsequent to hepatic I/R. When HC‐specific (Alb‐TLR4−/−) and myeloid‐cell–specific (Lyz‐TLR4−/−) TLR4 knockout (KO) mice were subjected to warm hepatic ischemia, there was significant protection in these mice, compared to wild type (WT). However, the protection afforded in these two strains was significantly less than global TLR4 KO (TLR4−/−) mice. DC‐specific TLR4−/− (CD11c‐TLR4−/−) mice had significantly increased hepatocellular damage, compared to WT mice. Circulating levels of high‐mobility group box 1 (HMGB1) were significantly reduced in Alb‐TLR4−/− mice, compared to WT, Lyz‐TLR4−/−, CD11c‐TLR4−/− mice and equivalent to global TLR4−/− mice, suggesting that TLR4‐mediated HMGB1 release from HCs may be a source of HMGB1 after I/R. HCs exposed to hypoxia responded by rapidly phosphorylating the mitogen‐activated protein kinases, c‐Jun‐N‐terminal kinase (JNK) and p38, in a TLR4‐dependent manner; inhibition of JNK decreased release of HMGB1 after both hypoxia in vitro and I/R in vivo. Conclusion: These results provide insight into the individual cellular response of TLR4. The parenchymal HC is an active participant in sterile inflammatory response after I/R through TLR4‐mediated activation of proinflammatory signaling and release of danger signals, such as HMGB1. (HEPATOLOGY 2013)